2003
DOI: 10.1021/la026912r
|View full text |Cite
|
Sign up to set email alerts
|

Formation of n-Alkanethiolate Self-Assembled Monolayers onto Gold in Aqueous Micellar Solutions of n-Alkyltrimethylammonium Bromides

Abstract: We have investigated the kinetics of formation for n-alkanethiolate self-assembled monolayers (SAMs) onto gold in aqueous micellar solutions of n-alkyltrimethylammonium bromides (C m TAB; m = 12, 14, 16, and 18). The cationic micelles provide hydrophobic domains to solubilize the alkanethiols and facilitate their delivery to the gold surface. The kinetics results for SAM formation in aqueous micellar solutions of C m TAB are well described by a first-order Langmuir adsorption model. The measured rate constant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 34 publications
3
34
0
Order By: Relevance
“…Yan et al reported the preparation of alkanethiolate SAMs (n = 8-18) formed onto gold from aqueous solutions containing micelles of ionic or nonionic surfactants. Interestingly, compared to the equivalent SAMs prepared from an ethanolic solution, these SAMs showed an overall increased chain density, as deduced from infrared spectroscopy experiments, and a higher electrochemical blocking ability, this result can be explained by the hydrophobic interactions in aqueous environment [6][7][8][9]. These authors also reported that the n-alkanethiols SAMs obtained from liquid and super-critical carbon dioxide exhibit similar crystallinities but greater packing densities when compared to SAMs formed from ethanol [10][11].…”
Section: Introductionmentioning
confidence: 84%
“…Yan et al reported the preparation of alkanethiolate SAMs (n = 8-18) formed onto gold from aqueous solutions containing micelles of ionic or nonionic surfactants. Interestingly, compared to the equivalent SAMs prepared from an ethanolic solution, these SAMs showed an overall increased chain density, as deduced from infrared spectroscopy experiments, and a higher electrochemical blocking ability, this result can be explained by the hydrophobic interactions in aqueous environment [6][7][8][9]. These authors also reported that the n-alkanethiols SAMs obtained from liquid and super-critical carbon dioxide exhibit similar crystallinities but greater packing densities when compared to SAMs formed from ethanol [10][11].…”
Section: Introductionmentioning
confidence: 84%
“…In order to adjust the electrical conditions at different interfaces encountered in practice, various types of SAMs were developed in the past and used in different contexts such as patterning of nanoscale devices, corrosion prevention, and controlling surface properties [518,[552][553][554][562][563][564][565][566][567][568][569][570][571][572][573][574]. SAM modification of a metal surface offers a better possibility to improve the performance of OE devices as well [518,[562][563][564][565][566][567][568][569][570][571][572][573][574].…”
Section: Interface Engineering For Os Devicesmentioning
confidence: 99%
“…SAM modification of a metal surface offers a better possibility to improve the performance of OE devices as well [518,[562][563][564][565][566][567][568][569][570][571][572][573][574]. The formation of SAMs on a metal surface, in the present context of OFETs, is basically meant for improving the contact properties across a semiconductor-metal interface.…”
Section: Interface Engineering For Os Devicesmentioning
confidence: 99%
See 2 more Smart Citations